PERAN KEPALA MADRASAH DALAM MEMBANGUN SEKOLAH ALTERNATIF: (Studi Kasus Pada Madrasah Ibtdaiyah Muhammadiyah Braja Asri - Way Jepara, Lampung Timur) - Apri Kurniasih (LPPM STAI DARUSSALAM LAMPUNG, 2014)
The objective of this research is to depict the process of building an effectiveschool, a qualitative approach is used to conduct this research in which thedata is collected through interview, observation, and documentation. Thedata, then, is analyzed through three steps namely data reduction, datadisplay, and data verivication. Some test like credibility, transferability,dependability, and confirmability are used to test the validity of the data.The finding of this research shows that: the process of building an effectiveschool of Islamic elementary school of Muhammadiya Braja Asri isinitiated by the headmaster through clarifying the objectives of the school,collaborating with the student’s parent, monitoring the student’s progress,enhancing the student’s skill through talent guiding every Saturday, andtraining to improve the teachers and staff’s commitment on education.